Microwave airflow drying of pecans at variable microwave power. (20th November 2018) - Zhang, Jigang; Li, Maoye; Ding, Zhien; Cheng, Jianghua; Yang, Song; Liu, Xinmin
Abstract: In this study, the dielectric properties of two varieties of pecan nuts at different moistures (10–30% w.b.), temperatures (25–85°C) were determined and the effect of microwave (MW) power density (0.8–2.6 W/g) and exposure time (30–300 s) on moisture content of pecan were approximated by response surface analysis. According to a comprehensive assessment of these results, phased varying power design for MW‐assisted air drying (PPMAD) was appropriate designed to dry pecan nuts. The result indicated that the penetration depths of MW at 2, 455 MHz to pecan nuts was distributed in the range of 4.05–10.45 cm in terms of different moisture content and temperature. The moderate output power density (1.7 W/g) is an optimized parameter during the primary stage of MW drying. In PPMAD scheme, 1.7 W/g was delivered in first 150 s, followed by cooling 30 s, and 2.6 W/g was applied in the final 120 s. The results showed that the hybrid drying of PPMAD was efficacious, leading to water losses of 19% in pecan and 16% in hickory without affecting their major compositions and sensory qualities. Further preservation showed that the oxidation degree of PPMAD‐dried nuts was lower than that of the control after 90 days of storage. Practical applications: Microwave hybrid drying has been reported to process food and provides a significantly increased shelf‐life for fruits and vegetables, such as apples, carrots, oranges, tomatoes, and spinach. There are no literatures focused on the parameter optimization of microwave drying on pecan and hickory during exposure. The present study provide an optimal method of microwave hybrid using a phased varying power design for MW‐assisted air drying which supply a foundation for large‐scale industrial applications of microwave drying.